Declines in the frequency of melanic Adalia bipunctata (Coleoptera: Coccinellidae) in Northern UK populations - Emily A. HORNETT; Jack ARCHER; Gregory D. D. HURST (European Journal of Entomology)
The two-spot ladybird, Adalia bipunctata, is polymorphic for elytral colour pattern. Whilst colour pattern polymorphism is complex, there are two predominant morphs: melanic and typical, which vary spatially in frequency. In the UK the melanic form has historically been most common in the industrialized North West of England. Evidence from industrial midland populations showed a decline in melanic frequency between 1960 and 1986 concordant with de-industrialization. We resampled the population of Merseyside in the North West of England, where the highest frequencies of melanic forms were historically observed, and compared our samples to data previously collected in 1962-1963. Data was consistent with a decline in frequency of melanics in the 60 year interval, but the melanic form was nevertheless still observed at around 30% frequency. We estimate the melanic allele has declined from 60-67% frequency to 13-18% frequency over the last 60 years, and that selection favouring the typical form has been of the order of 5-7% per generation. We note that selection against melanics in Wirral/Merseyside has been less strong than that observed in other Northern populations. We conclude that the decline in the melanic form is consistent with industrial thermal melanism as a primary factor driving melanism, but de-industrialization has not been sufficient to cause complete loss of the melanic allele in this location.